Bilateral Olecranon and Left Lesser Trochanter Avulsion Fractures in Renal Osteodystrophy: A Rare Case Report and Comprehensive Review - Papineni, Vijay; Botchu, Rajesh; Iyengar, Kartikeyan P.; Chapala, Shashank; Shah, Asad Rabbani; Rathinavelu, Balamurugan (Acta medica Lituanica, 2025)
Chronic Kidney Disease-Mineral and Bone Disorder (CKD-MBD) disrupts phosphorus and calcium metabolism, leading to skeletal disorders such as demineralization, weakened bones, and an increased fracture risk. These disorders, known as renal osteodystrophy, vary widely and are classified into secondary hyperparathyroidism, adynamic bone, and osteomalacia based on bone turnover. Fracture risk increases with the severity of CKD, particularly in advanced stages (creatinine clearance <15–20 mL/min), but even patients with mild to moderate CKD are at risk of fractures. Fractures of the Lesser Trochanter (LT) in adults are rare, and most are caused by underlying malignancies. We present a case of simultaneous avulsion fractures in the left lesser trochanter and bilateral olecranon processes secondary to minor trauma in a young patient with End Stage Renal Disease, which has not been previously reported, and review the literature. This review summarizes the role of imaging (Radiography, US, Computed Tomography, and Magnetic Resonance Imaging) in assessing avulsion fractures in patients with end-stage renal disease. Ultrasound serves as a supportive tool in evaluating the neuromusculoskeletal system; however, in patients with end-stage renal disease, radiography, CT, and MRI remain the primary imaging modalities for assessing avulsion fractures.